Greenhouse gas emissions from tractor-based rice paddy preparation in Thailand - Sangwijit, Prapragon; Sangwijit, Chonyitree (Asian Journal of Agriculture and Rural Development, 2026)
Greenhouse gas (GHG) emissions from agricultural machinery are critical to advise sustainable rice cultivation. According to the Intergovernmental Panel on Climate Change (IPCC) guidelines, GHG emissions were calculated based on observed fuel consumption rates. We used a 36-horsepower diesel tractor during soil preparation in paddy field sizes (0.04, 0.08, 0.16, 0.24, 0.32, and 0.48 hectares). The three evaluated implements were as follows: a vertical disc plough, a rotary tiller, and a harrow. The results show that the relationship between the field capacity of tractors and plot size was significantly positive. Meanwhile, technical time loss from implement lifting tended to decrease in large plots due to tractors’ improved maneuverability, compared to smaller plots. The highest emission profile was the first tillage stage, followed by the second tillage stage and the harrowing stage, respectively. CO2 amounts released from the first tillage stage, the second tillage stage, and the harrowing were 40.82, 35.80, and 17.67 CO2e kilogram/hectare, respectively. Total GHG emissions from three tillage stages decreased with increasing plot size; the largest plot had the lowest GHG emissions (79.64 CO2e kilogram/hectare). Larger paddy fields required lower fuel consumption rates, reduced GHG emissions, and minimized technical time losses. Land consolidation and precision leveling could substantially cut emissions from Thai rice farming.